Students’ Perceptions on the Application of Standardized English Language Proficiency Test as Graduation Requirement in Tourism Higher Education in Indonesia (A Case Study at Trisakti School of Tourism) - Rahayu, Nurti (Jurnal Penelitian Pariwisata, 2019)
The growing importance of English competence in various industries is one of the pull factors of the increasing need of English Language Proficiency (ELP) for university graduates. One of the ways to motivate students’ English competence is to set English language proficiency as graduation benchmark. This study aims to describe students’ perspectives on such policy and how it affects the students’ learning. A descriptive qualitative research is employed. A questionnaire is used to gain the primary data. The research participants are students of Trisakti School of tourism who has experienced such policy. The questionnaires comprise of two parts: demographic data and questions of students’ perceptions on various aspects on the usage of English language proficiency tests. Students’ perception on various campus program to improve English competence is also asked. The results reveal that students are familiar with the international standardized tests such as TOEIC, TOEFL and IELTS and they do make various preparation for the tests. As much as 60% of the respondents agree with the campus policy to set TOEIC and TOEFL score for graduation requirements. As for students’ perception on campus program, the results reveal that awarding scholarship for the top achiever students and live in program in English speaking program are considered to be the most effective program. The least effective programs are class grouping based on test score. The results can be of a valuable source for policy makers in the institution to develop a more effective program ti improve the students’ English competence.